1984
DOI: 10.1073/pnas.81.8.2322
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evidence for the in vivo occurrence of (2'-5')adenylyladenosine oligonucleotides in eukaryotes and prokaryotes.

Abstract: A monoclonal antibody highly specific for (2'-5')adenylyladenosine oligonucleotides was used together with a 125I-labeled analog of this compound to detect and quantify phosphorylated and nonphosphorylated (2'-5')adenylyladenosine oligonucleotides in a variety of tissues and cells. These oligonucleotides were first assayed as a whole in perchloric acid extracts and then further individually characterized by HPLC analysis. Their sensitivity to alkaline phosphatase, snake venon phosphodiesterase, and T2 RNase wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The findings reported here demonstrate conclusively the occurrence of 7-5' oligoadenylates in the prokaryote E. coli and confirm our preliminary observations [2]. The earlier experiments were done with bacteria grown in nutrient broth and led to the demonstration of the occurrence of the dimer, trimer and tetramer 5'OH 2'-5' oligoadenylates.…”
Section: Discussionsupporting
confidence: 79%
“…The findings reported here demonstrate conclusively the occurrence of 7-5' oligoadenylates in the prokaryote E. coli and confirm our preliminary observations [2]. The earlier experiments were done with bacteria grown in nutrient broth and led to the demonstration of the occurrence of the dimer, trimer and tetramer 5'OH 2'-5' oligoadenylates.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, a dominant negative mutant of endoribonuclease suppresses the anti-EMCV antiviral effect of interferon . Other reports have demonstrated the presence of 2-5A oligomers in different tissues of mouse and significantly enhanced levels during virus infection (Laurence et al, 1984;. Besides a possible role in mediating resistance to virus infection, the 2-A system has also been implicated in the control of cell growth and differentiation (Williams and Sil-verman, 1985;Hassel et al, 1993;Rysiecki et al, 1989;Kimchi et al, 1981aKimchi et al, , 1981bFerbus et al, 1985;Krause et al, 1985).…”
mentioning
confidence: 99%
“…A partial loss of the antiviral effects of IFN was seen in cells deficient in the (2'-5') oligo A synthetase (Salzberg et al, 1983), deficient in the (2'-5') oligo A-activated RNase F (Epstein et al, 1981) or when this RNase was inhibited by (2'-5')A analogs (Watling et al, 1985) although this is probably not the only mechanism by which IFN inhibits virus growth (Lebleu and Content, 1982). The (2'-5') oligo A nucleotides have been detected in many eukaryotic cells and even in bacteria (Laurence et al, 1984) and 2'-specific synthetase may be widespread. The mammalian IFN-induced enzyme has been purified from mouse (Dougherty et al, 1980) and human cells (Yang et al, 1981;Revel et al, 1981); a large and a small form of the enzyme have been observed St.…”
Section: Introductionmentioning
confidence: 99%